PENGARUH MODAL, TENAGA KERJA DAN PRODUKSI TERHADAP TINGKAT PENDAPATAN - Wahyuningsih, Roy (Institut Penelitian Dan Pengambangan Mandalika Indonesia (IP2MI), 2023)
This research is motivated by advances in science and technology which results in a very high level of competition between companies. The purpose of this research is to find out how much influence capital, labor and production have on increasing income in the home furniture industry at UD Meubel Jati Makmur, Trawasan Village Sumobito District, Jombang Regency. This study uses a type of quantitative research. The population in this study is data on financial statements of capital, labor, production and income in the home industry of UD Meubel Jati Makmur, Trawasan Village, Sumobito District, Jombang Regency. The sample in this study is 36 with time series data. Processing and analysis of data is done using SPSS. The results of this study indicate that: (1) there is no effect of capital on the level of income in the home industry of UD Meubel Jati Makmur, Trawasan Village, Sumobito District, Jombang Regency, (2) there is an influence of labor on the level of income in the home industry of UD Meubel Jati Makmur, Trawasan Village Sumobito District, Jombang Regency, (3) there is no effect of production on income levels in the UD Meubel Jati Makmur home industry, Trawasan Village, Sumobito District, Jombang Regency.